Effect Of Non-Oral Stimulation With Field Massage On The Time Of Onset And Achievement Of Independent Oral Feeding And Weight GainIn Premature Infants - Naghmeh Razaghi; najmeh zabihi torbati; hamidreza behnam vashani; mohammad Heidarzadeh (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Aim: One of the biggest problems of premature babies is oral feeding problems and delay in reaching independent oral feeding. The aim of the present study is to investigate the effect of non-oral stimulation with massage on the time of starting and achieving independent oral feeding and weighing in premature infants. Materials and Methods: Randomized clinical trial, 60 premature babies of 28-32 weeks in the NICU department of Ommolbanin Hospital, Mashhad met the criteria for entering the study, were selected and placed in two groups of field massage and control by simple random allocation. In the intervention group, infants received field massage (twice a day) for 15 minutes for 7 days, and the control group received the usual care. The two groups were compared with each other in variables of starting oral feeding, achieving independent oral feeding, and weight gain rate with statistical tests (T test, Manvitny & Covariance). A significance level of 0.05 was considered. Results: The mean and standard deviation of the gestational age of the infants in the intervention group was 29.0±1.1 and in the control group was 29.1±1.0 weeks. The results showed that the intervention group compared to the control group had a statistically significant difference in the beginning of oral feeding (p = 0.01) and the weight difference on the first and seventh days (p = 0.001), but even though nutritional progress to eight times of oral feeding in the intervention group was two days faster than the control group, but this difference was not significant (p = 0.17). Conclusion: Since non-oral stimulation with field massage can be effective in speeding up the time of oral feeding and weight gain of premature infants; it is recommended to be used by nurses in neonatal intensive care units to improve the quality of nursing care.